Anti-crack plastering mortar and preparation method thereof
By adding modified glass fiber and thiol fluorine-containing latex powder to the plaster mortar, crack-resistant plaster mortar is prepared, which solves the problem of traditional plaster mortar being susceptible to moisture and causes cracks, and significantly improves crack resistance and service life.
Patent Information
- Application Number
- CN202411832323.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
AI Technical Summary
Traditional plastering mortar is prone to moisture during use, causing cracks on the wall, affecting the aesthetics of the building and the stability of the structure.
By putting cement, sodium alginate, modified glass fiber, machined sand, gypsum, diatomaceous earth, fly ash and thiol fluorine-containing latex powder into a mixer and mixing evenly, and adding clean water while stirring, a crack-resistant plastering mortar was prepared.
The crack-resistant plastering mortar significantly improves the crack resistance and adhesion of the mortar by introducing modified glass fiber and thiol fluorine-containing latex powder, extends the service life of the building exterior walls, and reduces maintenance costs and environmental impacts.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to an anti-cracking plaster mortar and a preparation method thereof. Background Art
[0002] In the field of construction, plaster mortar is one of the important building materials, used for wall leveling and decoration. It generally has two functions: one is to enhance the wall's ability to resist moisture, weathering, and heat, and improve the durability of the wall; the other is to improve indoor sanitary conditions, purify the air, beautify the environment, and improve living comfort.
[0003] However, traditional plaster mortar is easily affected by factors such as environmental stress and temperature changes during use, and is easily affected by moisture, causing cracks in the wall, which not only affects the aesthetics of the building, but may also affect the stability and service life of the structure.
[0004] Prior art CN105776993A discloses an anti-cracking plaster mortar, which includes the following components by weight: 200-220 parts of ordinary Portland cement, 780-800 parts of engineering sand, 1-1.5 parts of polypropylene fiber, and 0.5-0.6 parts of ordinary mortar additives. However, its main anti-cracking component is polypropylene fiber, but the anti-cracking effect of the above fiber is limited.
[0005] CN101717232A discloses a high-performance lightweight composite mortar, characterized in that the materials and contents thereof are as follows: 250-350 parts of cement, 120-200 parts of reinforcing material, 160-200 parts of composite thermal insulation aggregate, 0.5-2.0 parts of short fibers, 0.2-1.5 parts of hydrophobic agent, 0.5-2.0 parts of thickener, 5-10 parts of redispersible powder, and 300-400 parts of slag sand. The mortar lacks improvement in crack resistance. The material has good thermal insulation effect, but insufficient crack resistance.
[0006] Therefore, developing a crack-resistant plaster mortar and a preparation method thereof is of great practical significance for improving the crack resistance of the plaster mortar. The applicant aims to solve the problem of insufficient crack resistance of the plaster mortar in the prior art. Summary of the invention
[0007] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a crack-resistant plaster mortar and a preparation method thereof: by putting cement, sodium alginate, modified glass fiber, machine-made sand, gypsum, diatomaceous earth, fly ash and mercapto fluorine-containing latex powder into a mixer, stirring evenly to obtain a mixture, adding clean water to the mixture while stirring, stirring evenly to obtain a crack-resistant plaster mortar, which solves the problem that traditional plaster mortar is easily affected by moisture during use, resulting in cracks on the wall, which not only affects the aesthetics of the building, but may also affect the stability and service life of the structure.
[0008] The purpose of the present invention can be achieved by the following technical solutions: A crack-resistant plaster mortar comprises the following components in parts by weight: 200-250 parts of cement, 10-16 parts of sodium alginate, 5-19 parts of modified glass fiber, 600-700 parts of machine-made sand, 50-60 parts of gypsum, 30-40 parts of diatomaceous earth, 30-40 parts of fly ash, 12-28 parts of mercapto-containing fluorine latex powder and 350-400 parts of clean water; Wherein, the modified glass fiber is prepared by the following steps: Step a1: placing the glass fiber in a vacuum drying oven, drying it at a temperature of 300-350° C. for 2-3 hours, then cooling it to room temperature, then adding it to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, then adding anhydrous acetone and stirring the reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 20-30 minutes, then heating it to reflux and continuing to stir the reaction for 3-4 hours, and after the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, and the precipitate is washed with anhydrous ethanol and distilled water for 2-3 times in sequence, and then placed in a vacuum drying oven, and dried at a temperature of 60-65° C. for 2-3 hours to obtain a pretreated glass fiber; Step a2: adding γ-glycidyloxypropyltrimethoxysilane and anhydrous ethanol to a three-necked flask equipped with a stirrer and a thermometer, and then stirring the mixture for 10-15 minutes at a temperature of 25-30°C and a stirring rate of 300-400 r / min, then adding nano silicon carbide powder and continuing to stir the mixture for 10-15 minutes, and then heating the mixture to 60-65°C and continuing to stir the mixture for 40-60 minutes. After the reaction is completed, the reaction product is cooled to room temperature to obtain a fiber coating liquid; Step a3: Add the pretreated glass fiber, fiber coating liquid and deionized water to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 30-40 minutes at an ultrasonic power of 200-300W, then stir and react for 10-15 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adjust the pH to 4-5 with glacial acetic acid, and then continue to stir and react for 1.5-2.5 hours at a temperature of 80-85°C. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with anhydrous ethanol and distilled water for 2-3 times in turn, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 2-3 hours to obtain modified glass fiber.
[0009] As a further solution of the present invention: the usage ratio of the glass fiber and anhydrous acetone in step a1 is 5g:40-45mL.
[0010] As a further solution of the present invention: the glass fiber in step a1 is a glass fiber with an average diameter of 11 μm and an average length of 19 mm.
[0011] As a further solution of the present invention: the usage ratio of the γ-glycidyloxypropyltrimethoxysilane, anhydrous ethanol and nano-silicon carbide powder in step a2 is 0.5-2.5g:50-55mL:5-15g.
[0012] As a further solution of the present invention: the average particle size of the nano silicon carbide powder in step a2 is 30 nm.
[0013] As a further solution of the present invention: the usage ratio of the pretreated glass fiber, fiber coating liquid and deionized water in step a3 is 3g:45-50mL:5-10mL.
[0014] As a further solution of the present invention: the mercapto fluorine-containing latex powder is prepared by the following steps: γ-Mercaptopropyltrimethoxysilane, methyl methacrylate, acrylamide, styrene, dodecafluoroheptyl methacrylate, emulsifier, azobisisobutyronitrile, deionized water and ethyl acetate are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 10-15min, and then the mixture is heated to 65-70°C and the stirring reaction is continued for 6-8h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. The mixture is then placed in a vacuum drying oven and dried at a temperature of 50-55°C for 2-3h, and then crushed through a 50-100 mesh sieve to obtain a mercapto fluorine-containing latex powder.
[0015] As a further scheme of the present invention: the usage ratio of γ-mercaptopropyltrimethoxysilane, methyl methacrylate, acrylamide, styrene, dodecafluoroheptyl methacrylate, emulsifier, azobisisobutyronitrile, deionized water and ethyl acetate is 3-7g:8-12g:10-15g:1-7g:1.5-8.5g:2-4g:0.5-1.5g:50-60mL:20-30mL.
[0016] As a further solution of the present invention: the emulsifier is a mixture of octadecyltrimethylammonium chloride and lauryl polyoxyethylene ether-20 in a mass ratio of 1:1-2.
[0017] As a further solution of the present invention: a method for preparing crack-resistant plaster mortar comprises the following steps: Step 1: Weigh 200-250 parts of cement, 10-16 parts of sodium alginate, 5-19 parts of modified glass fiber, 600-700 parts of machine-made sand, 50-60 parts of gypsum, 30-40 parts of diatomaceous earth, 30-40 parts of fly ash, 12-28 parts of mercapto-containing fluorine latex powder and 350-400 parts of clean water according to weight parts, and set aside; Step 2: Put cement, sodium alginate, modified glass fiber, machine-made sand, gypsum, diatomaceous earth, fly ash and mercapto-containing fluorinated latex powder into a mixer, and stir evenly to obtain a mixture; Step 3: Add clean water to the mixture while stirring, stir evenly to obtain crack-resistant plaster mortar.
[0018] Beneficial effects of the present invention: The invention discloses an anti-cracking plaster mortar and a preparation method thereof. The method comprises the following steps: placing cement, sodium alginate, modified glass fiber, machine-made sand, gypsum, diatomaceous earth, fly ash and mercapto-fluorinated latex powder into a mixer, stirring evenly to obtain a mixture, adding clean water into the mixture while stirring, stirring evenly to obtain the anti-cracking plaster mortar. The anti-cracking plaster mortar effectively disperses and absorbs external stress by introducing modified glass fiber, reduces the generation of cracks, and improves the anti-cracking performance of the mortar. The introduction of mercapto-fluorinated latex powder can significantly improve the bonding force between the mortar and the base layer, ensures that the plaster layer is firm and reliable, and improves the waterproof performance of the mortar, can prevent the mortar from being eroded by water, further inhibits the cracking phenomenon of the mortar during use, prolongs the service life of the building exterior wall, and makes the building safer and more stable. The preparation method is simple and easy to implement, the required raw materials are easily available, the cost is low, and it is suitable for large-scale industrial production, while also greatly reducing the maintenance cost and environmental impact.
[0019] In the process of preparing the anti-cracking plaster mortar, a modified glass fiber is first prepared. The glass fiber is first calcined and extracted with acetone to effectively remove surface impurities and enhance surface roughness to obtain pretreated glass fiber. Then, the pretreated glass fiber is treated with γ-glycidyloxypropyltrimethoxysilane and nano-silicon carbide powder. The nano-silicon carbide powder is loaded on the surface of the pretreated glass fiber. Then, after the γ-glycidyloxypropyltrimethoxysilane is hydrolyzed, the pretreated glass fiber can be wrapped and a large number of epoxy groups are introduced to obtain modified glass fiber. The glass fiber has excellent mechanical properties and can greatly improve the mechanical properties and crack resistance of the mortar. After loading the nano-silicon carbide powder, its mechanical properties can be further improved, and after being wrapped, its dispersion performance can be greatly improved. It can be evenly dispersed in the mortar, and after introducing a large number of epoxy groups, it can be connected to the mortar by chemical bonds, which greatly improves the performance of the mortar; in the process of preparing the crack-resistant plaster mortar, a mercapto-containing fluorine latex powder is also prepared, and methyl methacrylate, acrylamide, styrene, and dodecafluoroheptyl methacrylate are used as polymerization monomers to form a polymer, and γ-mercaptopropyltrimethoxysilane can use the mercapto group on it to undergo a click chemical reaction with the olefin group on the polymerization monomer, and can be grafted to introduce a large number of siloxane groups to obtain a mercapto-containing latex powder; the mercapto-containing latex powder has excellent elasticity and can greatly improve the mechanical properties of the mortar, and the large number of silicon atoms and fluorine atoms introduced can significantly reduce its surface energy, give the mortar high hydrophobicity, significantly improve its water resistance, avoid moisture erosion of the mortar, and improve its durability. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0021] This embodiment is a method for preparing a crack-resistant plaster mortar, comprising the following steps: Step S1: placing 5 g of glass fiber with an average diameter of 11 μm and an average length of 19 mm in a vacuum drying oven, drying at a temperature of 300° C. for 2 h, then cooling to room temperature, and then adding it to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, then adding 40 mL of anhydrous acetone and stirring the reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, then heating to reflux and continuing to stir the reaction for 3 h, and after the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, and the precipitate is washed twice with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 2 h to obtain a pretreated glass fiber; Step S2: 0.5 g of γ-glycidyloxypropyltrimethoxysilane and 50 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and then stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 10 min, and then 5 g of nano-silicon carbide powder with an average particle size of 30 nm was added and continued to stir for reaction for 10 min, and then the temperature was raised to 60° C. and continued to stir for reaction for 40 min. After the reaction was completed, the reaction product was cooled to room temperature to obtain a fiber coating liquid; Step S3: 3 g of pretreated glass fiber, 45 mL of fiber coating liquid and 5 mL of deionized water are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 30 min under the condition of an ultrasonic power of 200 W, and then stirred for reaction at a temperature of 25 ° C and a stirring rate of 300 r / min for 10 min, and then adjusted to pH 4 with glacial acetic acid, and then heated to 80 ° C and continued to stir for 1.5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is washed twice with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 60 ° C for 2 h to obtain modified glass fiber; Step S4: 3g of γ-mercaptopropyltrimethoxysilane, 8g of methyl methacrylate, 10g of acrylamide, 1g of styrene, 1.5g of dodecafluoroheptyl methacrylate, 2g of octadecyltrimethylammonium chloride, and an emulsifier prepared by mixing lauryl alcohol polyoxyethylene ether-20 in a mass ratio of 1:1, 0.5g of azobisisobutyronitrile, 50mL of deionized water, and 20mL of ethyl acetate are added to a three-necked flask equipped with a stirrer, a thermometer, and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25°C and a stirring rate of 300r / min for 10min, and then the mixture is heated to 65°C and the stirring reaction is continued for 6h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. The mixture is then placed in a vacuum drying oven and dried at a temperature of 50°C for 2h, and then crushed through a 50-mesh sieve to obtain a mercapto fluorine-containing latex powder; Step S5: weigh 200 parts of cement, 10 parts of sodium alginate, 5 parts of modified glass fiber, 600 parts of machine-made sand, 50 parts of gypsum, 30 parts of diatomaceous earth, 30 parts of fly ash, 12 parts of mercapto-containing fluorine latex powder and 350 parts of clean water according to weight parts, and set aside; Step S6: putting cement, sodium alginate, modified glass fiber, machine-made sand, gypsum, diatomaceous earth, fly ash and mercapto-containing fluorinated latex powder into a mixer, and stirring evenly to obtain a mixture; Step S7: adding clean water to the mixture while stirring, stirring evenly to obtain anti-cracking plaster mortar. Example 2
[0022] This embodiment is a method for preparing a crack-resistant plaster mortar, comprising the following steps: Step S1: 5 g of glass fiber with an average diameter of 11 μm and an average length of 19 mm is placed in a vacuum drying oven, dried at a temperature of 325° C. for 2.5 h, then cooled to room temperature, and then added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and then 42 mL of anhydrous acetone is added and stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the temperature is raised to reflux and the stirring reaction is continued for 3.5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged, and the precipitate is washed twice with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 62° C. for 2.5 h to obtain a pretreated glass fiber; Step S2: 1.5 g of γ-glycidyloxypropyltrimethoxysilane and 52 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and then stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 12 min, and then 10 g of nano-silicon carbide powder with an average particle size of 30 nm was added and continued to stir for reaction for 12 min, and then the temperature was raised to 62° C. and continued to stir for reaction for 50 min. After the reaction was completed, the reaction product was cooled to room temperature to obtain a fiber coating liquid; Step S3: 3 g of pretreated glass fiber, 48 mL of fiber coating liquid and 8 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 35 min at an ultrasonic power of 250 W, and then stirred for reaction at a temperature of 28 ° C and a stirring rate of 350 r / min for 12 min, and then adjusted to pH 4.5 with glacial acetic acid, and then heated to 82 ° C and continued to stir for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged, and the precipitate was washed twice with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 62 ° C for 2.5 h to obtain modified glass fiber; Step S4: 5g of γ-mercaptopropyltrimethoxysilane, 10g of methyl methacrylate, 12g of acrylamide, 4g of styrene, 5g of dodecafluoroheptyl methacrylate, 3g of octadecyltrimethylammonium chloride, and an emulsifier prepared by mixing lauryl alcohol polyoxyethylene ether-20 in a mass ratio of 1:1.5, 1g of azobisisobutyronitrile, 55mL of deionized water, and 25mL of ethyl acetate were added to a three-necked flask equipped with an agitator, a thermometer, and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28°C and a stirring rate of 350r / min for 12min, and then the mixture was heated to 68°C and the stirring reaction was continued for 7h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at a temperature of 52°C for 2.5h, and then crushed through a 75-mesh sieve to obtain a mercapto fluorine-containing latex powder; Step S5: weigh 225 parts of cement, 13 parts of sodium alginate, 12 parts of modified glass fiber, 650 parts of machine-made sand, 55 parts of gypsum, 35 parts of diatomaceous earth, 35 parts of fly ash, 20 parts of mercapto-containing fluorine latex powder and 375 parts of clean water according to weight parts, and set aside; Step S6: putting cement, sodium alginate, modified glass fiber, machine-made sand, gypsum, diatomaceous earth, fly ash and mercapto-containing fluorinated latex powder into a mixer, and stirring evenly to obtain a mixture; Step S7: adding clean water to the mixture while stirring, stirring evenly to obtain anti-cracking plaster mortar. Example 3
[0023] This embodiment is a method for preparing a crack-resistant plaster mortar, comprising the following steps: Step S1: placing 5 g of glass fiber with an average diameter of 11 μm and an average length of 19 mm in a vacuum drying oven, drying at a temperature of 350° C. for 3 h, then cooling to room temperature, and then adding it to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, then adding 45 mL of anhydrous acetone and stirring the reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, then heating to reflux and continuing to stir the reaction for 4 h, and after the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, and the precipitate is washed 3 times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain a pretreated glass fiber; Step S2: 2.5 g of γ-glycidyloxypropyltrimethoxysilane and 55 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and then stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 15 min, and then 15 g of nano-silicon carbide powder with an average particle size of 30 nm was added and continued to stir for reaction for 15 min, and then the temperature was raised to 65° C. and continued to stir for reaction for 60 min. After the reaction was completed, the reaction product was cooled to room temperature to obtain a fiber coating liquid; Step S3: 3 g of pretreated glass fiber, 50 mL of fiber coating liquid and 10 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 40 min at an ultrasonic power of 300 W, and then stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 15 min, and then adjusted to pH 5 with glacial acetic acid, and then heated to 85° C. and continued to stir for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed 3 times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain a modified glass fiber; Step S4: 7g of γ-mercaptopropyltrimethoxysilane, 12g of methyl methacrylate, 15g of acrylamide, 7g of styrene, 8.5g of dodecafluoroheptyl methacrylate, 4g of octadecyltrimethylammonium chloride, and an emulsifier prepared by mixing lauryl alcohol polyoxyethylene ether-20 in a mass ratio of 1:2, 1.5g of azobisisobutyronitrile, 60mL of deionized water, and 30mL of ethyl acetate were added to a three-necked flask equipped with an agitator, a thermometer, and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30°C and a stirring rate of 400r / min for 15min, and then the mixture was heated to 70°C and the stirring reaction was continued for 8h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at a temperature of 55°C for 3h, and then crushed through a 100-mesh sieve to obtain a mercapto fluorine-containing latex powder; Step S5: weigh 250 parts of cement, 16 parts of sodium alginate, 19 parts of modified glass fiber, 700 parts of machine-made sand, 60 parts of gypsum, 40 parts of diatomaceous earth, 40 parts of fly ash, 28 parts of mercapto-containing fluorine latex powder and 400 parts of clean water according to weight parts, and set aside; Step S6: putting cement, sodium alginate, modified glass fiber, machine-made sand, gypsum, diatomaceous earth, fly ash and mercapto-containing fluorinated latex powder into a mixer, and stirring evenly to obtain a mixture; Step S7: adding clean water to the mixture while stirring, stirring evenly to obtain anti-cracking plaster mortar.
[0024] Comparative Example 1: This comparative example is a method for preparing a crack-resistant plaster mortar, comprising the following steps: Step S1: weigh 250 parts of cement, 16 parts of sodium alginate, 700 parts of machine-made sand, 60 parts of gypsum, 40 parts of diatomaceous earth, 40 parts of fly ash and 400 parts of clean water according to weight parts, and set aside; Step S2: putting cement, sodium alginate, machine-made sand, gypsum, diatomaceous earth and fly ash into a mixer, and stirring evenly to obtain a mixture; Step S3: adding clean water to the mixture while stirring, stirring evenly to obtain anti-cracking plaster mortar.
[0025] Comparative Example 2: This comparative example is a method for preparing a crack-resistant plaster mortar, comprising the following steps: Step S1: placing 5 g of glass fiber with an average diameter of 11 μm and an average length of 19 mm in a vacuum drying oven, drying at a temperature of 350° C. for 3 h, then cooling to room temperature, and then adding it to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, then adding 45 mL of anhydrous acetone and stirring the reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, then heating to reflux and continuing to stir the reaction for 4 h, and after the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, and the precipitate is washed 3 times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain a pretreated glass fiber; Step S2: 2.5 g of γ-glycidyloxypropyltrimethoxysilane and 55 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and then stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 15 min, and then 15 g of nano-silicon carbide powder with an average particle size of 30 nm was added and continued to stir for reaction for 15 min, and then the temperature was raised to 65° C. and continued to stir for reaction for 60 min. After the reaction was completed, the reaction product was cooled to room temperature to obtain a fiber coating liquid; Step S3: 3 g of pretreated glass fiber, 50 mL of fiber coating liquid and 10 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 40 min at an ultrasonic power of 300 W, and then stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 15 min, and then adjusted to pH 5 with glacial acetic acid, and then heated to 85° C. and continued to stir for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed 3 times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain a modified glass fiber; Step S4: weigh 250 parts of cement, 16 parts of sodium alginate, 19 parts of modified glass fiber, 700 parts of machine-made sand, 60 parts of gypsum, 40 parts of diatomaceous earth, 40 parts of fly ash and 400 parts of clean water according to weight parts, and set aside; Step S5: putting cement, sodium alginate, modified glass fiber, machine-made sand, gypsum, diatomaceous earth and fly ash into a mixer, and stirring evenly to obtain a mixture; Step S6: Add clean water to the mixture while stirring, stir evenly, and obtain anti-cracking plaster mortar.
[0026] Comparative Example 3: This comparative example is a method for preparing a crack-resistant plaster mortar, comprising the following steps: Step S1: 7g of γ-mercaptopropyltrimethoxysilane, 12g of methyl methacrylate, 15g of acrylamide, 7g of styrene, 8.5g of dodecafluoroheptyl methacrylate, 4g of octadecyltrimethylammonium chloride, and an emulsifier prepared by mixing lauryl alcohol polyoxyethylene ether-20 in a mass ratio of 1:2, 1.5g of azobisisobutyronitrile, 60mL of deionized water, and 30mL of ethyl acetate are added to a three-necked flask equipped with a stirrer, a thermometer, and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30°C and a stirring rate of 400r / min for 15min, and then the mixture is heated to 70°C and the stirring reaction is continued for 8h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. The mixture is then placed in a vacuum drying oven and dried at a temperature of 55°C for 3h, and then crushed through a 100-mesh sieve to obtain a mercapto fluorine-containing latex powder; Step S2: weigh 250 parts of cement, 16 parts of sodium alginate, 700 parts of machine-made sand, 60 parts of gypsum, 40 parts of diatomaceous earth, 40 parts of fly ash, 28 parts of mercapto-containing fluorine latex powder and 400 parts of clean water according to weight parts, and set aside; Step S3: putting cement, sodium alginate, machine-made sand, gypsum, diatomaceous earth, fly ash and mercapto-containing fluorinated latex powder into a mixer, and stirring evenly to obtain a mixture; Step S4: adding clean water to the mixture while stirring, stirring evenly to obtain anti-cracking plaster mortar.
[0027] The anti-cracking plaster mortar of Examples 1-3 and Comparative Examples 1-3 was evenly applied on the wall surface, the first application thickness was 3 mm, and the second application was performed after it was naturally dried, the application thickness was 4 mm, and then it was naturally dried for 30 days. The performance of the formed cured samples was tested, and the test results are shown in the following table:
[0028] Referring to the data in the above table, according to the comparison between Examples 1-3 and Comparative Examples 1-3, it can be known that the addition of modified glass fiber can significantly improve the mechanical properties and crack resistance of the anti-cracking plaster mortar, and the addition of mercapto-containing fluorine latex powder can significantly improve the hydrophobic and water-resistant properties of the anti-cracking plaster mortar. Under the synergistic effect of the two, the comprehensive performance of the anti-cracking plaster mortar is excellent.
[0029] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0030] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined in this application, they shall all fall within the protection scope of the present invention.
Claims
1. A crack-resistant plaster mortar, characterized in that: It comprises the following components in parts by weight: 200-250 parts of cement, 10-16 parts of sodium alginate, 5-19 parts of modified glass fiber, 600-700 parts of machine-made sand, 50-60 parts of gypsum, 30-40 parts of diatomaceous earth, 30-40 parts of fly ash, 12-28 parts of mercapto-containing fluorine latex powder and 350-400 parts of clean water; Wherein, the modified glass fiber is prepared by the following steps: Step a1: placing the glass fiber in a vacuum drying oven, drying it at a temperature of 300-350° C. for 2-3 hours, then cooling it to room temperature, then adding it to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, then adding anhydrous acetone and stirring the reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 20-30 minutes, then heating it to reflux and continuing to stir the reaction for 3-4 hours, and after the reaction is completed, the reaction product is cooled to room temperature, then centrifuged, and the precipitate is washed with anhydrous ethanol and distilled water for 2-3 times in sequence, and then placed in a vacuum drying oven, and dried at a temperature of 60-65° C. for 2-3 hours to obtain a pretreated glass fiber; Step a2: adding γ-glycidyloxypropyltrimethoxysilane and anhydrous ethanol to a three-necked flask equipped with a stirrer and a thermometer, and then stirring the mixture for 10-15 minutes at a temperature of 25-30°C and a stirring rate of 300-400 r / min, then adding nano silicon carbide powder and continuing to stir the mixture for 10-15 minutes, and then heating the mixture to 60-65°C and continuing to stir the mixture for 40-60 minutes. After the reaction is completed, the reaction product is cooled to room temperature to obtain a fiber coating liquid; Step a3: Add the pretreated glass fiber, fiber coating liquid and deionized water to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 30-40 minutes at an ultrasonic power of 200-300W, then stir and react for 10-15 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adjust the pH to 4-5 with glacial acetic acid, and then continue to stir and react for 1.5-2.5 hours at a temperature of 80-85°C. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with anhydrous ethanol and distilled water for 2-3 times in turn, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 2-3 hours to obtain modified glass fiber.
2. The anti-cracking plaster mortar according to claim 1, characterized in that: The usage ratio of the glass fiber and anhydrous acetone in step a1 is 5g:40-45mL.
3. The anti-cracking plaster mortar according to claim 1, characterized in that: The glass fiber in step a1 has an average diameter of 11 μm and an average length of 19 mm.
4. The anti-cracking plaster mortar according to claim 1, characterized in that: The usage ratio of the γ-glycidyloxypropyltrimethoxysilane, anhydrous ethanol and nano-silicon carbide powder in step a2 is 0.5-2.5g:50-55mL:5-15g.
5. The anti-cracking plaster mortar according to claim 1, characterized in that: The average particle size of the nano silicon carbide powder in step a2 is 30 nm.
6. The anti-cracking plaster mortar according to claim 1, characterized in that: The usage ratio of the pretreated glass fiber, fiber coating liquid and deionized water in step a3 is 3g:45-50mL:5-10mL.
7. The anti-cracking plaster mortar according to claim 1, characterized in that: The mercapto fluorine-containing latex powder is prepared by the following steps: γ-Mercaptopropyltrimethoxysilane, methyl methacrylate, acrylamide, styrene, dodecafluoroheptyl methacrylate, emulsifier, azobisisobutyronitrile, deionized water and ethyl acetate are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 10-15min, and then the mixture is heated to 65-70°C and the stirring reaction is continued for 6-8h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. The mixture is then placed in a vacuum drying oven and dried at a temperature of 50-55°C for 2-3h, and then crushed through a 50-100 mesh sieve to obtain a mercapto fluorine-containing latex powder.
8. The anti-cracking plaster mortar according to claim 7, characterized in that: The dosage ratio of the γ-mercaptopropyltrimethoxysilane, methyl methacrylate, acrylamide, styrene, dodecafluoroheptyl methacrylate, emulsifier, azobisisobutyronitrile, deionized water and ethyl acetate is 3-7g: 8-12g: 10-15g: 1-7g: 1.5-8.5g: 2-4g: 0.5-1.5g: 50-60mL: 20-30mL.
9. The anti-cracking plaster mortar according to claim 7, characterized in that: The emulsifier is a mixture of octadecyl trimethyl ammonium chloride and lauryl alcohol polyoxyethylene ether-20 in a mass ratio of 1:1-2.
10. A method for preparing crack-resistant plaster mortar, characterized in that: The following steps are involved: Step 1: Weigh 200-250 parts of cement, 10-16 parts of sodium alginate, 5-19 parts of modified glass fiber, 600-700 parts of machine-made sand, 50-60 parts of gypsum, 30-40 parts of diatomaceous earth, 30-40 parts of fly ash, 12-28 parts of mercapto-containing fluorine latex powder and 350-400 parts of clean water according to weight parts, and set aside; Step 2: Put cement, sodium alginate, modified glass fiber, machine-made sand, gypsum, diatomaceous earth, fly ash and mercapto-containing fluorinated latex powder into a mixer, and stir evenly to obtain a mixture; Step 3: Add clean water to the mixture while stirring, stir evenly to obtain anti-cracking plaster mortar.
Citation Information
Patent Citations
High-performance lightweight composite mortar
CN101717232A
Anti-cracking plastering mortar
CN105776993A